Interaction Peculiarities of Gold(III) with Silica Gels Containing Both Aminopropyl and Mercaptopropyl Surface Groups - A.K. Trokhimchuk; E.B. Andrianova; V.N. Losev (Adsorption Science & Technology)
Sorption processes on the surfaces of chemically modified silica gels containing both mercaptopropyl and aminopropyl groups were examined. It was established that gold(III) sorption on the surfaces of such heteroligand silica gels involved the formation of complexes with sulphur- or nitrogen-containing ligands. The heteroligand complexes of gold(III) were not formed on the surfaces of the gels. This behaviour was attributed to the different spatial location of covalently bonded complexes with the surface aminopropyl and mercaptopropyl groups on the silica gel surface.